Laju Aliran Massa Fluida Pada Material Karbon Bambu Betung Dengan Variasi Temperatur Karbonisasi 400, 500, 600, 700, Dan 800 Oc - Hutagalung, Alvin Dio; Wijaksana, Hendra; Prananda Surya, I Gede Teddy (Teknik Desain Mekanika; Vol 11 No 1 (2022): Januari 2022 : Teknik Desain Mekanika, 2022)
Abstract Along with the times and the continued increase in the population, it has an impact on social changes in people's lives, one of which is comfort in activities. Indonesia is a tropical country so the use of air conditioning is needed, one of which is the Evaporative Air Cooler which uses the principle of a direct evaporative cooling system, the cooling effect is given by the evaporation process that occurs in the pad material that has been wetted by water. The pad material in this direct evaporative cooling system is a cooling medium derived from local bamboo, namely bamboo betung. This study uses carbon charcoal as a pad material to determine the effect of the mass flow rate of the fluid on the direct evaporative cooling system. By using a carbonization temperature of 400 oC, 500 oC, 600 oC, 700 oC, 800 oC. The results of all tests show that the specimen that has been carbonized with a temperature of 600oC or KRB 600 has the highest mass flow rate characteristic of 12.8x10-8 kg/s which can be used as potential for making new pad materials in the direct system. evaporative cooling Keywords: Direct evaporative cooling, bamboo betung, carbonization, The mass flow rate of the fluid